Impact of balanced versus unbalanced fluid resuscitation on clinical outcomes in critically ill children: protocol for a systematic review and meta-analysis - Lehr, Anab R; Rached-d’Astous, Soha; Parker, Melissa; McIntyre, Lauralyn; Sampson, Margaret; Hamid, Jemila; Menon, Kusum (Université d'Ottawa | University of Ottawa, 2019)
Abstract Background Isotonic crystalloid fluid bolus therapy is used in critically ill children to restore or maintain hemodynamic stability. However, the ideal choice of crystalloid remains to be determined. The most easily available and most frequently used crystalloid is 0.9% saline, an unbalanced crystalloid, that has been associated with hyperchloremic metabolic acidosis and acute kidney injury (AKI). Balanced fluids such as Ringer’s lactate (RL) were developed to be closer to the composition of serum. However, they are more expensive and less readily available than 0.9% saline. Few trials have found RL to be associated with more favorable outcomes, but pediatric data is limited and inconsistent. The objective of the present systematic review is to review existing literature to determine the effect of balanced versus unbalanced fluid bolus therapy on metabolic acidosis in critically ill children. Methods Using the Preferred Reporting Items for Systematic Review and Meta-analysis Protocols (PRISMA-P) guidelines, we will conduct a systematic review to retrieve all controlled trials and observational studies comparing balanced and unbalanced resuscitative fluids in critically ill children from age 28 days to 18 years old in any resuscitation settings. Search strategy was developed in collaboration with an experienced clinical research librarian. The primary outcome is the incidence and/or time to resolution of metabolic acidosis. Secondary outcomes included the incidence of hyperchloremia, AKI, duration of renal replacement therapy, vasopressors, mechanical ventilation, total volume of rehydration needed per day, extracorporeal membrane oxygenation, and length of stay and mortality. Study screening, inclusion, data extraction, and assessment of risk of bias will be performed independently by two authors. We intend to perform a meta-analysis with studies that are compatible on the basis of population and outcomes. Discussion Isotonic crystalloid fluid bolus therapy is a ubiquitous treatment in resuscitation of critically ill pediatric patients and yet there is no clear recommendation to support the choice of balanced versus unbalanced fluid. The present review will summarize current available data in the literature and assess whether recommendations can be generated regarding the choice of crystalloids or otherwise identify knowledge gaps which will open the door to a large-scale randomized controlled trial (RCT).